The most popular local and traditional food dishes in different regions of the Kingdom of Saudi Arabia and their cultural significance - Alqurashi, Randah M.; Abdalla, Samar M.; Bin Ammar, Albandari; Shatwan, Israa M.; Alsayegh, Abdulrahman A.; Alnasser, Aseel N.; Alfadhliah, Jewaher T.; Alnoubi, Atheer A.; Fallata, Ghadir A.; Alhumaidan, Omar A.; Bawazeer, Nahla M. (Frontiers in Nutrition, 2025)
IntroductionThis study aims to systematically identify and classify local and traditional dishes consumed across different regions of the Kingdom of Saudi Arabia (KSA), with a focus on understanding regional food consumption patterns and dietary diversity. By examining the culinary habits of households in Jazan, Jeddah, Al-Ahsa, Riyadh, and Hail, the study provides a comprehensive overview of the role that local and traditional foods play in shaping regional diets and cultural identity and aligning with the goals of Saudi Vision 2030.MethodsA descriptive cross-sectional study was conducted using 3-day food records from 75 households (900 food items) across five regions: Hail, Jazan, Al-Ahsa, Jeddah, and Riyadh.ResultsThe findings highlight the predominance of local dishes such as rice, eggs, vegetables, meat, and legumes in Saudi cuisine. In contrast, traditional culinary specialties—including soups, desserts, and date-based dishes—were consumed less frequently across all regions. Statistically significant differences were observed in the average number of local dishes among the regions (p < 0.05). The most traditional cuisines intake in Al- Ahsa, Riyadh, and Hail regions are “Harees with chicken,” and “Jreesh,”. “Masabib.” “Mufalak” and “Harees with chicken” constitute around 33.3% and 16.7% of the overall consumption of traditional food in the Al- Ahsa region, respectively. The low intake of traditional foods may impact both nutritional quality and cultural continuity.DiscussionStrengthening national efforts—particularly those led by the Saudi Culinary Arts Commission—is recommended to preserve and promote regional culinary heritage. This study underscores the potential of local and traditional foods to enhance cultural pride, support local economies, and improve dietary habits, thereby contributing to the broader objectives of economic diversification and tourism development outlined in Vision 2030.